Myosin 5a in the Urinary Bladder: Localization, Splice Variant Expression, and Functional Role in Neurotransmission - Carew, Josephine A.; Cristofaro, Vivian; Dasari, Suhas P.; Carey, Sean; Goyal, Raj K.; Sullivan, Maryrose P. (Frontiers in Physiology, 2022)
Dysregulation of neurotransmission is a feature of several prevalent lower urinary tract conditions, but the mechanisms regulating neurotransmitter release in the bladder are not completely understood. The unconventional motor protein, Myosin 5a, transports neurotransmitter-containing synaptic vesicles along actin fibers towards the varicosity membrane, tethering them at the active zone prior to reception of a nerve impulse. Our previous studies indicated that Myosin 5a is expressed and functionally relevant in the peripheral nerves of visceral organs such as the stomach and the corpora cavernosa. However, its potential role in bladder neurotransmission has not previously been investigated. The expression of Myosin 5a was examined by quantitative PCR and restriction analyses in bladders from DBA (dilute-brown-nonagouti) mice which express a Myosin 5a splicing defect and in control mice expressing the wild-type Myosin 5a allele. Functional differences in contractile responses to intramural nerve stimulation were examined by ex vivo isometric tension analysis. Data demonstrated Myosin 5a localized in cholinergic nerve fibers in the bladder and identified several Myosin 5a splice variants in the detrusor. Full-length Myosin 5a transcripts were less abundant and the expression of splice variants was altered in DBA bladders compared to control bladders. Moreover, attenuation of neurally-mediated contractile responses in DBA bladders compared to control bladders indicate that Myosin 5a facilitates excitatory neurotransmission in the bladder. Therefore, the array of Myosin 5a splice variants expressed, and the abundance of each, may be critical parameters for efficient synaptic vesicle transport and neurotransmission in the urinary bladder.